Analiza zmienności cen akcji KGHM Polska Miedź SA w latach 1998-2004 - Miłobędzki, Paweł; Nowak, Sabina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper is devoted to the modelling of the rate of return on KGHM Polska Miedź SA stocks based on the daily, weekly and monthly time series of variables exhibiting various sources of its risk associated with the copper forward contracts traded at the London Metal Exchange (LME) and Polish and British capital markets operation from the period January 5, 1998 - May 28, 2004. The natural logs of the copper spot price at LME, Warsaw and London stock exchanges indices WIG and FTSE100, and American dollar-Polish zloty exchange rate are found significant in the symmetric error correction model of natural logs of the rate of return on stock in question. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 36-47